The effects of teachers' homework follow-up practices on students' EFL performance: a randomized-group design - Rosário, Pedro; Núñez, José C.; Vallejo, Guillermo; Cunha, Jennifer; Nunes, Tânia; Suárez, Natalia; Fuentes, Sonia; Moreira, Tânia (Frontiers in Psychology, 2015)
This study analyzed the effects of five types of homework follow-up practices (i.e., checking homework completion; answering questions about homework; checking homework orally; checking homework on the board; and collecting and grading homework) used in class by 26 teachers of English as a Foreign Language (EFL) using a randomized-group design. Once a week, for six weeks, the EFL teachers used a particular type of homework follow-up practice they had previously been assigned to. At the end of the six weeks students completed an EFL exam as an outcome measure. The results showed that three types of homework follow-up practices (i.e., checking homework orally; checking homework on the board; and collecting and grading homework) had a positive impact on students’ performance, thus highlighting the role of EFL teachers in the homework process. The effect of EFL teachers’ homework follow-up practices on students’ performance was affected by students’ prior knowledge, but not by the number of homework follow-up sessions.